Neural Correlates of Activities of Daily Living in Frontotemporal Dementia. (March 2013) - Mioshi, E.; Hodges, J. R.; Hornberger, M.
Background: Little research to date has investigated neural correlates of functional disability in frontotemporal dementia (FTD). Methods: Activities of daily living (ADL) were covaried against gray matter atrophy regions via Voxel-based morphometry in FTD (n = 52) and contrasted against a dementia control Alzheimer disease (AD) group (n = 20) and healthy age-matched controls (n = 18). Results: Both patient groups had similar ADL scores. However, FTD and AD differed on the gray matter atrophy areas associated with ADL scores. The FTD showed involvement of prefrontal and thalamus regions while AD showed widespread temporal, parietal, frontal, and caudate atrophy correlating with ADL dysfunction. Importantly, only the left superior frontal gyrus was implicated in ADL dysfunction for both FTD and AD. Conclusions: Differences in underlying neural correlates of ADL impairment have important clinical implications as these differences should be taken into account when interventions are planned. Dementia subtypes might require specifically tailored interventions for functional disability.